Destruction, heritage and memory: post-conflict memorialisation for recovery and reconciliation - Atabay, Zeynep Ece; Macedonio, Alessandra; Teba, Tarek; Unal, Zeynep (EMERALD GROUP PUBLISHING LTD, 2024)
Purpose The destruction of armed confrontations - ranging from chronic armed conflicts to full-scale wars - leads to enormous loss of human lives and causes wide-scale devastation. They also leave deep and lasting traumas in the minds of those whose lives are torn apart because of a conflict. Memorialisation of conflict-affected sites plays an invaluable part in post-trauma recovery and can contribute to the reconciliation of different groups involved in a conflict as these sites are representatives of communities' collective memory, identity and a source of unity and resilience. This paper aims to investigate post-trauma recovery and reconciliation processes through the phenomena of memorialisation. It aims to answer how and if the memorialisation of sites of pain can contribute to the recovery and reconciliation of affected communities and serve as examples for other people around the world. Design/methodology/approach The documentation of such processes and the lessons learnt can offer valuable information for conducting similar exercises in other settings ravaged by a conflict. To achieve this, a review of literature on trauma, memory, memorialisation and difficult heritage was conducted, while the memorialisation processes from different cases such as Hiroshima and Nagasaki (1939-1945), Beirut (1975-1990) and Sarajevo's Vijecnica and Mostar Bridge (1992-1995) were analysed. Findings It was identified that the potential of memorialisation for post-trauma recovery and reconciliation is vast. However, if these processes can heal or hurt depend largely on who the stakeholders are; how the site and events are interpreted and presented; how pre/post-conflict relationships and dynamics are harnessed; how symbolic meanings (old and new) are [re]interpreted; the spatial-temporal nature of the site and those interacting with it; and the intended and perceived messages. Altogether, memorialisation of conflict-affected sites is a political and continuous process that should take into consideration all those directly and indirectly involved, the dynamics between them and all the symbolic meanings acquired and attributed to the site. Originality/value The study critically explores frameworks of memorialisation and their impact on both the built environment and communities. It contributes to the wider discussion of difficult heritage memorialisation and approaches to reflect on sites and cities emerging from crises such as conflict.
Keywords: Collective memory; Difficult heritage; Heritage-led reconciliation; Heritage-led recovery; Memorialisation; Sites of pain; CULTURAL-HERITAGE; HIROSHIMA; WAR; BOSNIA; Science & Technology - Other Topics